The future of transport between digitalization and decarbonization : trends, strategies and effects on energy consumption (2020)
We are at the dawn of a new transport era, characterized by accelerated innovation— particularly digital—and a growing pressure to reduce our CO2 emissions from all sectors of the economy, including transport. This new era is alive with exciting opportunities, as well as challenges. Swift policy action is required all across the globe to define and revise as appropriate legislative frameworks to put the sector on a sustainability path. Such frameworks must comprise policy measures to increase the efficiency of transport systems and the share of more sustainable modes to boost the uptake of clean vehicles, vessels, and aircraft, and replace fossil fuels with sustainable alternatives. Countries have also the duty to incentivize the right consumer choices and increase investment. Digitalization will drive the transition toward a more efficient transport system. It is important that all countries step up efforts to create a functional mobility data space. Policies must support the development of innovative, fully interoperable solutions, and incentivize their uptake. For example, countries need to deploy smart traffic management systems enabled by digitalization in order to increase and better manage the capacity of railways and inland waterways, to make best use of airspace, to reduce congestion, to introduce shared and automated mobility solutions, and to facilitate multimodal transport. On its side, the European Commission is tackling these challenges head-on, guided by the European Green Deal, which sets the target of making Europe’s economy climate-neutral by 2050. Transport is, rightfully, at the core of the European Green Deal and must reduce its emissions by 90% by 2050. Our strategy for sustainable and smart mobility addresses all of these areas and will guide the EU as we seek to reduce the environmental footprint of transport in the coming years and guide it toward climate neutrality by 2050.